Dimensions of Religiosity in a Collection of Short Stories “War Breaks Again In Gaza” (Satu Pena Palestine Humanitarian Anthology) - Febriani, Avinda Elsa; Roziah, Roziah (Journal of Language and Literature Studies, 2024)
This study explores the dimensions of religiosity that appear in the short stories contained in the book "War Breaks Out Again in Gaza: Satu Pena's Palestinian Humanitarian Anthology". In the humanitarian context of Palestine, this short story presents a narrative filled with religious overtones, depicting life experiences influenced by war and conflict in the region. Through text analysis and the concept of religiosity, this study aims to understand how religious values ??are reflected in short story narratives, as well as how the dimensions of religiosity provide a deeper understanding of the social and psychological conditions of the story characters. This study method involves text analysis and interpretation of cultural context to explore the dimensions of religiosity in short stories. The study findings show that this short story highlights the role of religion in shaping the identity and spiritual resilience of the characters in the midst of conflict. Values ??such as hope, steadfastness and community solidarity are described as key elements that characterize the dimension of religiosity. This study also investigates how conflict and suffering can strengthen or doubt the religious beliefs of story characters. This study contributes to an understanding of the complexity of the dimensions of religiosity in literary narratives, especially in the context of the Palestinian conflict and humanity. It is hoped that the results of the analysis will illustrate the way in which this short story integrates religious values ??to convey a humanitarian message and provide deeper insight into the realities of life amidst regional conflict.